(untitled) (Research, Society and Development, 2020)
Depression, as well as other mental disorders, has multifactorial causes and specific diagnostic criteria that serve as guidelines for a promising treatment. Imbalances of the intestine-brain axis, through dysbiosis of the intestinal microbiota, have proved to be important with psychiatric disorders and intestinal diseases. In this follow-up, the study aims to characterize the relationship between the deregulations directed from the gut-brain axis, specifically between dysbiosis and the psychopathology of depression. From searches in the PubMed, BVS and EBSCOhost databases, 8 articles were selected with the methodological criterion of being empirical and experimental for an integrative literature review. Dysbiosis and/or depression were induced via stress models in all animals used in the experiments. The bidirectionality of the axis was found in all the reviewed articles. Both dysfunctions affect each other, involving psychomotor, metabolic, and inflammatory responses, still possible therapeutic targets, elevate the rebalancing of the intestinal microbiome.